1989
DOI: 10.1073/pnas.86.4.1178
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a phorbol ester-repressible v-src-inducible gene.

Abstract: Chicken embryo fibroblasts (CEF) infected with a temperature-sensitive Rous sarcoma virus (RSV) mutant, tsNY72-4, express a set of pp60v-src-induced RNAs soon after shift to the permissive temperature. By subtractive and differential screening, we have cloned 12 of these sequences, 2 of which were c-fos and krox-24. Serum induced all the v-src-inducible genes tested, suggesting that these genes serve roles in normal cell division and are not specific to transformation per se. Significantly, however, v-src prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
174
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(177 citation statements)
references
References 36 publications
2
174
1
Order By: Relevance
“…These secreted, cysteine-rich proteins have been named members of the`CCN family' (for Cyr61/Cef10, CTGF/Fisp12, and Nov; Bork, 1993) and include at least three distinct members: cyr61/cef10 (Simmons et al, 1989;O'Brien et al, 1990), CTGF/®sp12 (Bradham et al, 1991;Ryseck et al, 1991) and nov Joliot et al, 1992). Members of this protein family share a high level of sequence homology, including complete conservation of 38 cysteine residues in their secreted portion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These secreted, cysteine-rich proteins have been named members of the`CCN family' (for Cyr61/Cef10, CTGF/Fisp12, and Nov; Bork, 1993) and include at least three distinct members: cyr61/cef10 (Simmons et al, 1989;O'Brien et al, 1990), CTGF/®sp12 (Bradham et al, 1991;Ryseck et al, 1991) and nov Joliot et al, 1992). Members of this protein family share a high level of sequence homology, including complete conservation of 38 cysteine residues in their secreted portion.…”
Section: Introductionmentioning
confidence: 99%
“…cef10, the chicken ortholog of cyr61, was also cloned as a growth factor-and v-src-inducible immediate-early gene (Simmons et al, 1989). ®sp12 was later found to be the mouse homolog of the human connective tissue growth factor (CTGF; Bradham et al, 1991), which was identi®ed by virtue of its mitogenic activity in human umbilical vein endothelial cells (HUVECs; Bradham et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Egr-1 is a zinc ®nger transcriptional factor (see Gashler and Sukhatme, 1995) which was also identi®ed as NGFI-A (Milbrandt, 1987), Zif268 (Lau and Nathans, 1987), Cef5 (Simmons et al, 1989), Krox24 (Lemaire et al, 1988) and Tis8 (Lim et al, 1987). Similar to c-Fos, Egr-1 expression is rapidly induced by mitogens such as platelet-derived growth factor (PDGF), FGF and epidermal growth factor (EGF) in ®broblasts (Sukhatme et al, 1987;Lau and Nathans, 1987;Lemaire et al, 1988), suggesting a possible role of Egr-1 in mediating bFGF autoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although CTGF exhibits PDGF-like biological activities and appears to be antigenically related to PDGF, it has little peptide sequence homology to either the PDGF A or B chain peptides. The peptide sequence of CTGF reveals that it is a member of a family of peptides including the v-src-induced CEF-10 peptide identified in src-transformed chicken embryo fibroblasts (Simmons et al, 1989), cyr6l cloned from mouse BALB/ c 3T3 fibroblasts after serum induction (O'Brien et al, 1990), and the serum-induced fispl2 (Ryseck et al, 1991) or TGF-,B-induced BIGM2 transcript identified in 3T3 cells (Brunner et al, 1991). CTGF is also related to the newly described nov gene product that is overexpressed in nephroblastomas induced by myeloblastosisassociated virus (Joliot et al, 1992).…”
Section: Introductionmentioning
confidence: 99%